Maintenance management of water treatment plant (government and private) / Muhammad Firdaus Kamaruzzaman - Kamaruzzaman, Muhammad Firdaus (Faculty of Architecture, Planning and Surveying, 2010)
Water treatment plant is the facility where treated water for user use for drinking, washing and all otter thing. In order to treated water, the water treatment plant requires careful attention in the maintenance of treatment plant. This is because it can cause problem of not achieving standard and it can bring unsatisfaction among the consumer. Generally in Malaysia they are two parties who are doing treatment to water process, first is by a government and the otherwise is done by the private. In this dissertation it will discuss more about maintenance management were practice and implement in the treatment plant under this two parties supervision. Beside that in this dissertation it will be found usually problem occur in the maintenance management where currently practice in two type of treatment plant. This dissertation finally comes out with rationale conclusion and recommendations were suitable to be implementing at treatment plant to overcome the problem that there facing.